Influence of twin-screw processing conditions on the mechanical properties of biocomposites - Alvarez, Vera Alejandra (2005)
In order to evaluate the effect of processing conditions, composites of MaterBi-Y matrix with 15 wt% sisal fibers are obtained with different temperature profiles and speeds of rotation of the screw, using a twin-screw extruder. Three different temperature profiles are selected. The speeds of rotation are 25, 60, and 80 rpm. The samples are obtained by compression at 180°C and 700 MPa for 10 min. The mechanical properties of composites increase when the rotation speed changes from 25 to 60 rpm and then decreases. Fiber breakage increases with rotational speed, but aspect ratio increases too. Increased modulus with fiber aspect ratio is easily understood because longer fibers carry more tensile loads as a result of increase in transfer length. The decrease in the mechanical properties at a high rotational speed can be due to the degradation of the matrix. The impact properties increase when temperature increases. The decrease in impact properties at temperatures above 185°C can be due to the thermal decomposition of the material.